Pengaruh Servant Leadership terhadap Kepuasan Kerja dan Kinerja Karyawan di STIE IBMT Surabaya - Iswati Iswati; Jimmy Ignatius; Gatot Prastowo (Jurnal Simki Economic, 2025)
This study aims to examine the Effect of Servant Leadership on Job Satisfaction and Employee Performance at STIE IBMT' Surabaya. Related variables in this study are Servant Leadership, Job Satisfaction and Employee Performance. The method used in this study seeks quantitative methods through distributing questionnaires to get 40 respondents. While the sampling technique in this study was non-probability, through the sample selection methop was purposive sampling and used data analysis techniques in the form of Structural Equation Modeling (SEM). As for the results of the study, among others, the Servant Leadership variable is proven to influence job satisfaction and also employee performance in a positive and significant way.